Penguatan Literasi Keuangan sebagai Upaya Meningkatkan Pengetahuan Keuangan dan Perilaku Keuangan di Desa Kanekes (Baduy) - Fitriah Fitriah; Yanto Nius Gulo; Khalifa Damalin Ayunda; Novia Novia; Mirna Agustin; Tia Patiah (Lembaga Pengembangan Kinerja Dosen, 2026)
Financial literacy is an essential aspect in supporting community financial management, particularly in rural and indigenous communities such as Kanekes Village (Baduy). Although the community has begun to access financial services and digital technology, their ability to manage finances remains limited. Therefore, this community service activity aims to identify the level of financial literacy and to encourage public awareness of better financial management. The method used is a descriptive qualitative approach through in-depth interviews and field observations. The results show that the community, especially in Baduy Luar, has utilized social media such as TikTok Live and Instagram for product marketing and has adopted digital payment systems such as QRIS through Bank BRI, although cash transactions still dominate. The main sources of income come from micro-enterprises based on local potential, including handicrafts, traditional clothing, accessories, and food products. However, the community generally lacks financial recording practices and structured financial planning, causing income to be directly spent on daily needs. The activity also indicates the emergence of initial awareness regarding financial management and highlights the role of youth as local leaders in adopting digital technology. Therefore, strengthening financial literacy is crucial to improving financial behavior and supporting sustainable economic transformation within the community.